EFEKTIVITAS INKUIRI TERBIMBING UNTUK MENINGKATKAN KEMAMPUAN LITERASI KIMIA SISWA - Yunita Sari; Emmawaty Sofya; Tasviri Efkar (Universitas Lampung, 2019)
This research was aimed to describe the effectiveness of guided inquiry to improve chemical literacy ability in electrolyte and non electrolyte solution topic. This research used quasi experiment with Pretest Posttest Control Group Design. The sample was obtained by cluster random sampling technique, and it was obtained sample was students of X MIA 5 as experiment class and X MIA 4 as control class. The effectiveness of guided inquiry was showed by the significant difference for average n-Gain of chemical literacy ability between the experiment and control class. The results showed that students chemical literacy ability were higher in the experimental calss compared to the control class. Based on the results of the research it can be concluded that effective guided inquiry and has a high effect size to improve the ability of chemical literacy in electrolyte and non electrolyte solution topic.Keywords: guided inquiry, chemical literacy, electrolyte and non electrolyte solutionPenelitian ini bertujuan untuk mendeskripsikan efektivitas inkuiri terbimbing untuk meningkatkan kemampuan literasi kimia siswa pada materi larutan elektrolit dan non elektrolit. Penelitian ini menggunakan metode quasi eksperimentdengan pretest-posttest control grup design. Pengambilan sampel pada penelitian ini dilakukan dengan cara cluster random sampling dan diperoleh kelas X MIA 5 sebagai kelas eksperimen dan kelas X MIA 4 sebagai kelas kontrol. Efektivitas inkuiri terbimbing ditunjukkan oleh perbedaan rata-rata n-Gain kemampuan literasi kimia yang signifikan antara kelas eksperimen dan kelas kontrol. Hasil penelitian menunjukkan kemampuan literasi kimia siswa tinggi pada kelas eksperimen dibandingkan kelas kontrol. Berdasarkan hasil penelitian dapat disimpulkan bahwa inkuiri terbimbing efektif dan mempunyai ukuran pengaruh yang besar dalam meningkatkan kemampuan literasi kimia siswa pada materi larutan elektrolit dan non elektrolit.Kata kunci: inkuiri terbimbing, literasi kimia, larutan elektrolit dan non elektrolit